Development Of Delta Amino Levulinic Acid Auxotrophic Of Vibrio Cholerae O1 El Tor Ogawa. [RC126. H352 2005 f rb] [Microfiche 7748]. - Abd Rashid, Nur Haslindawaty (2005)
Cholera is an important diarrheal disease in developing countries. WHO estimates that cholera caused 111,575 cases with 1,894 deaths in the year 2003 worldwide.